Investment estimation and acceptance of State Tax Instead of coal mining business license Clear and Clean in West Sumatra Province - Riam Marlina; Fachrurrozie Sjarkowi; Maulana Yusuf (Indonesian Journal of Environmental Management and Sustainability, 2018)
This research conceptual measurement simulation for financial component which is needed for investment and benefit simulation held by stated that taken from company obligation categorized as non tax for mining activities predicated with cnc at West Sumatera Province. This simulation connected with capital investment and operational activities that influenced by coal getting stripping ratio, coal hauling and other financial related. This simulation only values stated income non tax and royalty. Analysis methods using from several document feasibiliy study from coal company has already operated, and also estimation for all investment component and components of income stated non tax. Accuracy data accepted for this research at least 30% from all investment. Estimation starting from deciding production target, life mining period, investment needs, financial operation and other financial activities, and comparison with theoritical measurement. The comparison result then used to make another financial model simulation. At the last, this research will present economy simulation model created from mining operational activities in west sumatera province to estimate stated income non tax from mining production operational. Using sensitivity analysis, shows that the change of coal selling prices will gives significant influence to NPV project and stated incomen non tax.